2001
DOI: 10.1016/s0039-6060(01)79415-9
|View full text |Cite
|
Sign up to set email alerts
|

Raxofelast, a hydrophilic vitamin E-like antioxidant, stimulates wound healing in genetically diabetic mice*1

Abstract: The current study provides evidence that raxofelast restores wound healing to nearly normal levels in experimental diabetes-impaired wounds and suggests that an increased lipid peroxidation in diabetic mice may have a role in determining a defect of wound repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The following parameters were evaluated and scored: re-epithelialization, dermal matrix deposition and regeneration, granulation tissue formation and remodelling. The histological specimens were evaluated according to the score reported in the literature concerning wound healing in experimental models [20,2224]. …”
Section: Methodsmentioning
confidence: 99%
“…The following parameters were evaluated and scored: re-epithelialization, dermal matrix deposition and regeneration, granulation tissue formation and remodelling. The histological specimens were evaluated according to the score reported in the literature concerning wound healing in experimental models [20,2224]. …”
Section: Methodsmentioning
confidence: 99%
“…The fine balance of these nutrients has to be taken into account, though. For example, with vitamin E, an important lipophilic antioxidant, conflicting studies have both shown reduced tensile strength and collagen content of experimental wounds [13, 14] and, conversely, increased wound strength and collagen [15]. As with all aspects of wound repair, a fine balance is necessary to ultimately achieve proper healing.…”
Section: Physiologic Wound Healingmentioning
confidence: 99%
“…The negative effects of oxidative stress can be restrained by antioxidant enzyme systems and dietary antioxidants such as carotenoids 5. The carotenoid structure has a common chemical feature containing a long-conjugated double-bond polyene chain, which has an ability to quench or scavenge ROS 6. Several kinds of antioxidants are proposed to regulate the oxidation–reduction balance, and studies of the effects of various antioxidants on wound healing have reported accelerated healing outcomes 7,8…”
Section: Introductionmentioning
confidence: 99%